2021
DOI: 10.18678/dtfd.898373
|View full text |Cite
|
Sign up to set email alerts
|

Afrika’da COVID-19 Pandemisine karşı Alternatif Bir Çözüm Olarak Telesağlık Hizmetleri

Abstract: Technology is disrupting bringing up a better innovation and strengthening the healthcare services. Telehealth is one of these services. Telehealth can help in times of emergency situations as well as reducing morbidity caused by other diseases other than coronavirus and also constraining its spread as well as sustaining the country's economic development. Although, telehealth is a disruptive innovation, this article aimed to point out why Africa and rest of the world need telehealth to structure out the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
(30 reference statements)
0
16
0
1
Order By: Relevance
“…Furthermore, [37] found that the life expectancy increases while death rate reduces economic growth under the COVID-19 pandemic situation in Nigeria over the data period of 1989-2018.. Similarly, [38] found the reduction in CO 2 emissions while conducting a study considering the consequences of COVID-19 on the social isolation in the Chinese economy [39]. also noted that under global pandemic (COVID-19) condition, the necessary arrangements of tele-health facilities can play significant role in improving the human health in case of African nations.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Furthermore, [37] found that the life expectancy increases while death rate reduces economic growth under the COVID-19 pandemic situation in Nigeria over the data period of 1989-2018.. Similarly, [38] found the reduction in CO 2 emissions while conducting a study considering the consequences of COVID-19 on the social isolation in the Chinese economy [39]. also noted that under global pandemic (COVID-19) condition, the necessary arrangements of tele-health facilities can play significant role in improving the human health in case of African nations.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Future research could also investigate the effects of availability of telehealth in COVID-19 vaccine acceptance. 56 Regarding attitudinal factors, future research could investigate the effects of perceived self-efficacy about vaccines and perceived social cause of herd immunity.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Procedure: This qualitative study features an interpretative Phenomenological Analysis (IPA) approach (23). (N = 258) participants from Kaduna state's randomly selected six Local Government Areas (Chikun, Birnin Gwari, Ikara, Makarfi, and Kaura Local Government Area) who were healthcare workers (HCW), traditional birth attendance (TBA), traditional head leader (THL), adolescent/youth, and pregnant women in the previous 8-10 months (see Table 3).…”
Section: Participants Andmentioning
confidence: 99%